Characteristics of Wasathiyah Morals in Ibn Kathir's Tafsir - Hasibuan, Khoirul Umri (Yayasan Salam Cerdas Al-Fattah, 2024)
Akhlaq Washatiyah, or moderate morality, is one of the important aspects of Islamic ethics that emphasizes the importance of balance and moderation in every aspect of life. This concept is very relevant in the context of modern life, where extreme tendencies often appear in various aspects of life. This paper aims to examine the characteristics of akhlaq washatiyah in the Tafsir of Ibn Kathir, one of the most respected works of tafsir in the Islamic tradition. By examining the Tafsir of Ibn Kathir, a deeper understanding is obtained regarding how the concept of akhlaq washatiyah is applied in the interpretation of the verses of the Qur'an. This study uses a qualitative analysis method of relevant tafsir texts, with a special focus on the principle of moderation in behavior and attitudes proposed by Ibn Kathir. Through this analysis, it is hoped that it can be found how Ibn Kathir interprets the verses of the Qur'an by emphasizing the balance between the various demands of life, both in spiritual, moral, and social aspects. The results of the study show that Ibn Kathir strongly emphasizes the principle of balance and justice in his tafsir, which reflects the characteristics of akhlaq washatiyah. The interpretation teaches the importance of avoiding extremes in religion, as well as maintaining a moderate attitude in dealing with various situations. Thus, this study contributes to strengthening the understanding of the importance of morality washatiyah in everyday life, as well as how these values ​​of moderation can be applied in various contexts of modern life.